Modelos atômicos no livro didático de química: estudo das representações ilustrativas pelo viés do discurso científico-social - SILVA, Manuela Conceição Machado da (2020)
This work reports a research on the levels of representations of chemical knowledge treated in the Chemistry TextBook (CTB), with regard to the illustrations present in the content of Atomic Models (AM). The textbook is still the most present resource in the classroom despite the existence of innumerable didactic materials, it strongly influences students in the conception and construction of scientific knowledge. For the teaching of Chemistry, its use becomes essential for the exposition of chemical knowledge, and from it the student starts his contact with the scientific culture, its representation and language, so the study of this didactic material is very pertinent for understanding the process teaching and learning. Therefore, this research made use of the qualitative methodological perspective (LUDKE; ANDRE, 2012). With regard to the analytical typology used, it was decided to document analysis, since the object of analytical interest consisted of a chemistry set of books adopted in a public school sampling that offer high school located in the city of São Luís, Maranhão. The data analysis was carried out using the content analysis technique, guided by the studies of Bardin (1978) and Franco (2008), adopting categories based on the theory of Johnstone (1982; 1993) that deal with levels of knowledge representation chemical (Macroscopic, Submicroscopic and Symbolic) and reflecting on the contribution of images categorized according to references of social representation such as Moscovici (1981) for the appropriation of scientific language. Thus, nine Chemistry textbooks were analyzed and seven hundred and thirteen images from chapters dealing with MA were cataloged. First, a pre-analysis was carried out to characterize the study variables in reference to the type of illustrations: (i) photograph, (ii) figure, (iii) graph, (iv) diagram and (v) table. Then an exploratory study of the images separating them into illustrations of the indirect tract (comic strip and special sections dealing with the History of Chemistry and Science) and illustrations of the direct tract (images that represent objects and chemical phenomena). The direct treatment illustrations were categorized according to the levels of representation portrayed by the model developed by Johnstone (1982; 1993) and then treated from the perspective of the Theory of Social Representation. The results showed a large number of figure-type illustrations (48%). On the other hand, there was a marked deficit in relation to the insertion of graphic illustrations (1,5%). The categorization of the illustrations of the direct tract indicated that the Macroscopic and Submicroscopic categories presented the amounts of 24.2% and 24.4%, respectively. In general, it can be said that in the analyzed CTB a representational aspect prevails, that is, symbolic (28.1%) in their illustrations, which means that the emphasis given to the construction of chemical knowledge is directed towards the use of formulas , equations and reaction mechanism, which can make it difficult for the student to appropriate the body of knowledge about science objects and their representations.